Fungi the crucial contributors for nanotechnology: a green chemistry perspective - Moudgil, Aliesha; Chaudhari, Bhushan P. (Advancing Frontiers in Mycology & Mycotechnology, 2019)
Myconanotechnology has gained an exceptional momentum in today’s world. It encompasses a wide range of applications like in agriculture, biomedical, electronics, textiles, cell and molecular biology, nanodevices, and many more. This fast-growing research field has a list of many nanoparticles that have been synthesized from different kinds of fungi. It is an eco-friendly approach that has sidelined the conventional methods of chemical and physical synthesis that require high energy and are toxic and expensive. The fungal-based synthesis gains functionality due to its discrete and diversified advantages that are being explored. Various parameters like temperature, pH, time and concentrations of fungal biomass or extract as well as of the precursor play a vital role in the protocols. These factors have to be optimized for the laboratory as well as industrial scale production. A greater importance to the use of cell-free extracts for nanosynthesis has been given. They contain the enzymes that are reported to be involved in the synthesis mechanisms as reducing agents and capping agents. The role of fungi in nanosynthesis and nanotechnology per se has many patents under its name. Although there are voids in the existing synthesis methods as well as lacunae in the application part that need to be addressed and filled. With an extensive research and work, myconanoparticles can be exploited to the maximum and lead its advancement in new areas.

Eichhornia crassipes mediated bioinspired synthesis of crystalline nano silver as an integrated medicinal material: a waste to value approach - Moudgil, Aliesha; Deval, Animesh S.; Dharne, Mahesh S.; Sarkar, Dhiman M.; Choudhari, Amit S.; Chaudhari, Bhushan P. (Journal of Cluster Science, 2021)
The present study deals with the synthesis of silver nanoparticles from Eichhornia crassipes. Dynamic light scattering (DLS), Transmission electron microscopy (TEM), UV-Vis spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy and X-ray diffraction (XRD) were performed for nanoparticle characterization. The aqueous plant extract of Eichhornia crassipes was phytochemically analyzed for phenol, flavonoid, reducing sugar content, alkaloids, saponins and carotenoids. The synthesized particles after optimization of important parameters have an average diameter of 12.48 +/- 3.43 nm with a spherical morphology and zeta potential of - 31.53 mV. At 100 mu g/ml of nanoparticle concentration, the antioxidant activity of 93.6% was observed. MIC (Minimum inhibitory concentration) values exhibiting the antimicrobial attributes reported an estimated value of 7.8 mu g/ml for gram-negative and higher values of 31.25 and 250 mu g/ml for gram-positive bacteria. The antibiofilm assay showed 86.89% and 74.7% of the reduction in violacein synthesis and biofilm inhibition respectively at 15 mu g/ml nanoparticle concentration. The anticancer assay reported the IC50 (Inhibitory concentration) values of 13.32, 14.71 and 19.91 mu g/ml for HeLa, HCT 116 and L6 cell lines respectively. Thus the study establishes a significant integrative treatment to combat secondary infections in cancer patients. Graphic
Keywords: antibacterial activity; Antibiofilm activity; Anticancer activity; Antioxidant activity; Eichhornia crassipes; silver nanoparticles

One-pot concurrent biosynthesis of biphasic CuxO (cuprous and cupric oxide) nanoparticles using leaf extract of Eichhornia crassipes and investigation of their potent healthcare applications - Moudgil, Aliesha; Varma, Sanjana; Shinde, Manish D.; Vamkudoth, Koteswara Rao; Sarkar, Dhiman M.; Shende, Rajnigandha A.; Amalnerkar, Dinesh; Chaudhari, Bhushan P. (Emergent Materials, 2022)
Eichhornia crassipes, an aquatic weed, has been used for the one-pot quick synthesis of cuprous and cupric oxide nanoparticles in this report. The identification and validation of the formed nanoparticles were successfully done by sophisticated characterization techniques such as UV–visible spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. Their biomedical interventions were assessed by their antioxidant and anticancer activities. The synthesized nanoparticles have a spherical morphology with an average diameter of 10 nm. Antioxidant assay performed showed an increasing trend in a dose-dependent manner with the percentage radical scavenging activity up to 94.70% at a much higher concentration of 1000 µg/ml. The antioxidant potential at such higher concentration is suspected to invoke a change in the cytotoxic potential of the nanoparticles which is then verified by the MTT assay. A significant cytotoxic activity against HeLa (cervical cancer) and HCT 116 (colorectal carcinoma) cell lines was detected with noted IC50 values of 17.17 and 13.70 µg/ml respectively. The conclusive findings obtained are enough to substantiate the use of these nanoparticles in biomedical areas specifically in anticancer treatment due to their high toxicities. The hazards imposed by Eichhornia crassipes can be alleviated by using them as biofactories for the synthesis of a variety of nanomaterials. This helps in curbing the water pollution issues as well as the developing synthesis protocols for robust and stable nanoparticles.

Challenges and emerging strategies for next generation liposomal based drug delivery: an account of the breast cancer conundrum - Moudgil, Aliesha; Salve, Rajesh; Gajbhiye, Virendra; Chaudhari, Bhushan P. (Chemistry and Physics of Lipids, 2023)
The global cancer burden is witnessing an upsurge with breast cancer surpassing other cancers worldwide. Furthermore, an escalation in the breast cancer caseload is also expected in the coming years. The conventional therapeutic regimens practiced routinely are associated with many drawbacks to which nanotechnological in-terventions offer a great advantage. But how eminent could liposomes and their advantages be in superseding these existing therapeutic modalities? A solution is reflected in this review that draws attention to a decade-long journey embarked upon by researchers in this wake. This text is a comprehensive discussion of liposomes, the front runners of the drug delivery systems, and their active and passive targeting approaches for breast cancer management. Active targeting has been studied over the decade by many receptors overexpressed on the breast cancer cells and passive targeting with many drug combinations. The results converge on the fact that the actively targeted formulations exhibit a superior efficacy over their non-targeted counterparts and the all lipo-somal formulations are efficacious over the free drugs. This undoubtedly underlines the dominion of liposomal formulations over conventional chemotherapy. These investigations have led to the development of different liposomal formulations with active and passive targeting capacities that could be explored in depth. Acknowl-edging and getting a deeper insight into the liposomal evolution through time also unveiled many imperfections and unchartered territories that can be explored to deliver dexterous liposomal formulations against breast cancer and more in the clinical trial pipeline.
Keywords: Breast cancer; Liposomal metamorphosis; Receptor-ligand dynamics; Targeted Drug Delivery

Understanding critical aspects of liposomal synthesis for designing the next generation targeted drug delivery vehicle - Moudgil, Aliesha; Chaudhari, Bhushan P. (Chemistryselect, 2023)
We identified process parameters of the thin film hydration technique and intrinsic factors to synthesize liposomes for drug delivery. The thin film formation step impacted the nature of the lipid layer, and we optimized 240 RPM rotation speed, 700 mm of Hg vacuum pressure, and 2 ml of chloroform as the organic solvent. The hydration step controlled the particle specifications, and we optimized 270 RPM rotation speed, PBS as the hydrating medium, and 1 h hydration time. We obtained a comparatively smaller liposomal population with a lower size distribution just after hydrating the lipid layer that required milder downsizing steps -10 extrusion passes through a single polycarbonate membrane. The intrinsic factors including the concentrations and molar ratio of lipids affected the synthesis steps and the particle specifications. Characterization of liposomes by analytical techniques confirmed the synthesis of a monodisperse population with hydrodynamic diameter<150 nm, moderate stability, spherical morphology, and high thermal and storage stability. This comprehensive study defines the role of every parameter, provides a mechanistic insight into synthesis that is supported by experimental data, and helps tune specific parameters to synthesize liposomes for drug delivery or any application with desired specifications.
Keywords: carrier system; designing and characterization; drug delivery; liposomes; targeting moiety